Small cell osteosarcoma in gnathic bones in the maxilla: case report in a pediatric patient - Tayná Souza Gomes da Silva; Ilan Hudson Gomes de Santana; Helder Domiciano Dantas Martins; Raabe Carine Ferreira de Melo; Paulo Rogério Ferreti Bonan (Journal of Cancer Research and Clinical Oncology)
Abstract Small cell osteosarcoma (SCOS) is a rare variant of conventional osteosarcoma, characterized by tumor cells of small size and uniform morphology, which can lead to diagnostic confusion with other small cell tumors, requiring a detailed diagnostic approach. The manifestation in a child adds a degree of complexity, as the management of malignant tumours in paediatric patients requires specific considerations to minimize the long-term side effects of oncological treatment and preserve the structural and functional development of the orofacial region. This report concerns an 8-year-old female patient referred to the Oral and Maxillofacial Surgery outpatient clinic with progressive swelling in the right maxillofacial region, initially asymptomatic, but progressing to pain and difficulty chewing. A cone beam computed tomography scan was requested and an incisional biopsy was carried out for histopathological and immunohistochemical analysis, which confirmed the pathological entity. The lesion was then completely resected with a safety margin and the affected area removed to restore functionality and aesthetics. The surgical specimen was sent for further histopathological analysis, which confirmed the diagnosis of SCOS. Detailed immunohistochemical analysis was crucial to the diagnosis, and a comprehensive surgical approach was indicated given the aggressive behavior of the lesion. This report emphasizes the importance of an integrated multidisciplinary approach, combining oncology, pathology and oral and maxillofacial surgery.